Preoperative exercise induces endothelial progenitor cell mobilisation in patients undergoing major surgery – A prospective randomised controlled clinical proof-of-concept trial. Issue 9 (September 2022) - Bauer, Claus Juergen; Findlay, Michael; Koliamitra, Christina; Zimmer, Philipp; Schick, Volker; Ludwig, Sebastian; Gurtner, Geoffrey C.; Riedel, Bernhard; Schier, Robert
Abstract: Introduction: Prehabilitation is increasingly recognised as a therapeutic option to reduce postoperative complications. Investigating the beneficial effects of exercise on cellular mechanisms, we have previously shown that a single episode of exhaustive exercise effectively stimulates endothelial progenitor cells (a cell population associated with vascular maintenance, repair, angiogenesis, and neovascularization) in correlation with fewer postoperative complications, despite the ongoing debate about the appropriate cell surface marker profiles of these cells (common phenotypical definitions include CD45dim, CD133+, CD34+ and/or CD31+). In order to translate these findings into clinical application, a feasible prehabilitation programme achieving both functional and cellular benefits in a suitable timeframe to expedite surgery is necessary. Objective: The objective of this study was to test the hypothesis that a four-week prehabilitation programme of vigorous-intensity interval exercise training is feasible, increases physical capacity (primary outcome) and the circulatory number of endothelial progenitor cells within peripheral blood. Methods: In this unblinded, parallel-group, randomised controlled proof-of-concept clinical trial (German Clinical Trial Register number: DRKS00000527) conducted between 01 st December 2014 and 30 th November 2016, fifteen female adult patients scheduled for incontinence surgery with abdominal laparotomy at the University Hospital Cologne were allocated to either an exercise (n = 8, exclusion of 1 patient, analysed n = 7) or non-exercise group (n = 7, exclusion of 1 patient, analysed n = 6). The exercise group's intervention consisted of a vigorous-intensity interval training for four weeks preoperatively. Cardiopulmonary Exercise Testing accompanied by peripheral blood collection was performed before and after the (non-)training phase. Cellular investigations were conducted by flow cytometry and cluster-based analyses. Results: Vigorous-intensity interval training over four weeks was feasible in the exercise group (successful completion by 8 out of 8 patients without any harms), with significant improvements in patients' functional capacity (increased oxygen uptake at anaerobic threshold [intervention group mean + 1.71 ± 3.20 mL/min/kg vs. control group mean −1.83 ± 2.14 mL/min/kg; p = 0.042] and peak exercise [intervention group mean + 1.71 ± 1.60 mL/min/kg vs. control group mean −1.67 ± 1.37 mL/min/kg; p = 0.002]) and a significant increase in the circulatory number of endothelial progenitor cells (proportionate CD45dim/CD14dim/CD133+/CD309+/CD34+/CD31 + subpopulation within the circulating CD45-pool [p = 0.016]). Conclusions: We introduce a novel prehabilitation concept that shows effective stimulation of an endothelial progenitor cell subpopulation within four weeks of preoperative exercise, serving as a clinical cell-mediated intervention with the aim to reduce surgical complications. Funding: Institutional funding. DFG (German Research Foundation, 491454339) support for the Article Processing Charge. Abstract : Endothelial progenitor cells; Preoperative exercise; Prehabilitation; Cluster-based analysis; Cell mobilisation; Postoperative complications.